Tribological investigations with near eutectic AlSi alloys found in engine vane pumps – Characterization of the material tribo-functionalities. (June 2020) - Summer, Florian; Pusterhofer, Michael; Grün, Florian; Gódor, István
Abstract: This paper gives attention to wear and friction processes of sliding contacts with cover parts of variable displacement engine vane pumps. Two near eutectic aluminium-silicon alloys for different casting processes were characterized by tribological investigations. This was done with the aid of specifically designed test methods on model scale as well as by damage analysis of real life parts from engine tests. The latter was additionally used as a validation measure for the model tests, which proved transferability of damage events from model tests to the engine parts. The results emphasize significance of the material structure of near eutectic AlSi materials on the wear performance. A pronounced load bearing structure of eutectic Si is able to provide high wear resistance. Highlights: Friction and wear characterization of engine vane pump components is presented. Wear -rates of similar near eutectic AlSi materials differs -depending on manufacture conditions and microstructures formed. Wear rankings of engine tests and ring on disc model test are similar. Protective tribofilms (rich in P, O, Zn, S) do form on Si phases.